Pengaruh Independensi, Kompetensi, Etika, Profesionalisme, dan Lingkungan Kerja Auditor terhadap Kualitas Audit: (Studi Empiris pada Kantor Akuntan Publik di Wilayah Jakarta) - Devan Adika Prasetya; Cris Kuntadi; Rachmat Pramukty (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study aims to determine the influence that can occur between: (1) Independence on Audit Quality, (2) Competence on Audit Quality, (3) Ethics on Audit Quality, (4) Professionalism on Audit Quality, (5) Work Environment on Audit Quality. The sample used in this study is external auditors who work in 7 Public Accounting Firms in the Jakarta Area. The number of respondents in this study was 78 respondents. The sampling technique used in this study is purposive sampling which is one of the techniques in the non-probability sampling group. The data collection method used in this study uses a questionnaire method. The design used in this study is hypothesis testing using SPSS statistical version 27. The results of this study show that (1) independence has a positive effect on audit quality, (2) competence has a positive effect on audit quality, (3) ethics has a positive effect on audit quality, (4) professionalism has a positive effect on audit quality, (5) work environment has a positive effect on audit quality.